Some Notes on the Growth and Increment of the Hundred-year Old Plantation of Eucalyptus globulus in the Nilgiris Hills - Borota, J. (Indian Forester, 1965)
In the mountainous conditions of the Nilgiris area in South India, the Eucalyptus globulus has a very good increment ability at the age of one hundred years. The tree diameter at breast height at the Tree Increment Plot No. I was ranging from d=81.7 centimetres (trees No. 23 and No. 82) to d=1804 centimetres (tree No. 60.) The current annual diameter increnlent is progressively increasing from the thinnest to the thickest trees. The current annual diameter increment of the average tree at the plantation is Î”dÂ¯= 7.3 millimetres. The variability of the diameter increment gradually decreases from the thinnest to the thickest trees. The current annual crop volume increment of the sample plot reaches about 26.0 cubic metres per hectare.